A fast-curing adhesive for cutting solar silicon wafers and a preparation method thereof

By modifying the fast curing stick glue of bisphenol A type epoxy resin and polythiol system, the problems of low production efficiency and insufficient mechanical performance of stick glue during photovoltaic silicon wafer cutting process are solved, and efficient and stable cutting process is achieved .

CN118725793BActive Publication Date: 2025-02-11JINWAN GAOJING SOLAR ENERGY TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410730088.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-06
Publication Date
2025-02-11
Estimated Expiration
2044-06-06

AI Technical Summary

Technical Problem

The existing photovoltaic silicon wafer cutting process has low production efficiency, high descending rate, edge collapse rate and rod drop rate, and the mechanical properties of the stick glue are insufficient, which affects stable cutting.

Method used

Fast curing adhesive rod glue with modified bisphenol A type epoxy resin and polythiol system is used to improve the hardness, adhesion and shear strength of the adhesive rod glue and reduce the surface dryness through nanomaterial modification and powder filler modification. time.

Benefits of technology

The mechanical properties of the stick glue are achieved, such as high hardness, strong adhesion and high shear strength, which reduces the descending rate, edge collapse rate and rod drop rate, and improves production efficiency and cutting stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004879959630000031
    Figure BDA0004879959630000031
  • Figure BDA0004879959630000101
    Figure BDA0004879959630000101
  • Figure BDA0004879959630000111
    Figure BDA0004879959630000111
Patent Text Reader

Abstract

The present invention relates to the field of photovoltaic single crystal silicon wafer processing, and in particular to a fast curing adhesive for solar silicon wafer cutting and a preparation method thereof. The fast curing adhesive for solar silicon wafer cutting provided by the present invention comprises component A and component B, wherein the component A comprises modified bisphenol A epoxy resin, glycidyl ester epoxy resin, modified powder filler, defoamer, anti-settling agent, colorant and coupling agent; the component B comprises polythiol, curing accelerator, defoamer, anti-settling agent, modified powder filler and thermoplastic toughening diluent; the modified bisphenol A epoxy resin is prepared by modifying bisphenol A epoxy resin with nanomaterials; the nanomaterial is prepared by modifying cellulose nanocrystals with tannic acid and methacrylic chloride. The adhesive prepared by the present invention has the advantages of high hardness, strong adhesion, high bonding shear strength, high bending strength, etc., excellent mechanical properties, short surface drying time and high curing efficiency. The adhesive prepared by the present invention can improve production efficiency and reduce the rate of wire stripping, edge collapse and rod drop while achieving stable cutting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of photovoltaic single crystal silicon wafer processing, and in particular to a fast-curing adhesive stick for cutting solar silicon wafers and a preparation method thereof. Background Art

[0002] With the development of the photovoltaic industry, the trend of photovoltaic silicon wafers becoming larger and thinner and the corresponding cutting wires becoming thinner has become an inevitable trend under the background of continuous cost reduction and efficiency improvement. The continuous advancement of photovoltaic silicon rod cutting technology has put forward higher requirements for the adhesive for the rods.

[0003] At present, the commonly used adhesive sticks are mostly epoxy-polythiol systems. For example, the Chinese patent "Adhesive sticks for thin-sheet silicon slices and its preparation method (publication number: CN110437779A)" discloses an AB two-component adhesive stick, which is suitable for thin-sheet silicon slices. Its A component includes epoxy resin, filler, defoamer, anti-settling agent and coupling agent, and its B component consists of polythiol, meta-phenylenediamine prepolymer, accelerator, filler, defoamer and anti-settling agent. When used, it was found that the invented product has the disadvantages of long pre-curing surface drying time, low bending strength, high chip drop rate, and high edge collapse rate.

[0004] With the continuous development of photovoltaic silicon rod cutting technology, the efficiency of sticking is in urgent need of improvement. However, due to the material system, the interfacial force between materials is low, such as the poor bonding between epoxy resin and filler and curing agent, and between filler and curing agent, which undoubtedly limits the curing efficiency and the mechanical properties of sticking glue (hardness, adhesion, shear strength and bending strength, etc.), hindering the improvement of production efficiency, edge collapse rate and stick drop rate. Therefore, it is urgent to develop a sticking glue for solar silicon wafer cutting with the advantages of high hardness, strong adhesion, high bonding shear strength, excellent mechanical properties, low surface drying time, high curing efficiency, and stable cutting, while being able to improve production efficiency and reduce edge collapse rate and stick drop rate. Summary of the invention

[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a fast-curing adhesive stick for cutting solar silicon wafers and a preparation method thereof. The adhesive stick prepared by the present invention has the advantages of high hardness, strong adhesion, high bonding shear strength, excellent mechanical properties, short surface drying time, and high curing efficiency. The adhesive stick prepared by the present invention can improve production efficiency, reduce the rate of wire stripping, the rate of edge collapse, and the rate of stick drop while achieving stable cutting, and effectively solves the problems of low production efficiency, high rate of wire stripping, the rate of edge collapse, and the rate of stick drop in the prior art silicon wafer cutting process.

[0006] The technical solution of the present invention is:

[0007] A fast-curing adhesive stick for cutting solar silicon wafers, comprising component A and component B, wherein the component A comprises modified bisphenol A epoxy resin, glycidyl ester epoxy resin, modified powder filler, defoamer, anti-settling agent, colorant and coupling agent; the component B comprises polythiol, curing accelerator, defoamer, anti-settling agent, modified powder filler and thermoplastic toughening diluent;

[0008] The modified bisphenol A epoxy resin is prepared by modifying the bisphenol A epoxy resin with a nano material; the nano material is prepared by modifying cellulose nanocrystals (CNC) with tannic acid (TA) and methacryloyl chloride (MC).

[0009] Furthermore, in the fast-curing adhesive stick for cutting solar silicon wafers, the component A includes the following components and their mass fractions: 40-70 parts of modified bisphenol A epoxy resin, 5-20 parts of glycidyl ester epoxy resin, 20-40 parts of modified powder filler, 0.1-3 parts of defoamer, 0.05-5 parts of anti-settling agent, 0.05-1 parts of colorant and 0.01-3 parts of coupling agent; the component B includes the following components and their mass fractions: 35-60 parts of polythiol, 2-10 parts of curing accelerator, 0.1-3 parts of defoamer, 0.05-5 parts of anti-settling agent, 15-30 parts of modified powder filler and 5-20 parts of thermoplastic toughening diluent.

[0010] Furthermore, the A component includes the following components and their mass fractions: 58 parts of modified bisphenol A epoxy resin, 8 parts of glycidyl ester epoxy resin, 30 parts of modified powder filler, 1.2 parts of defoamer, 0.4 parts of anti-settling agent, 0.4 parts of colorant and 2 parts of coupling agent; the B component includes the following components and their mass fractions: 55 parts of polythiol, 5 parts of curing accelerator, 1 part of defoamer, 2 parts of anti-settling agent, 25 parts of modified powder filler and 12 parts of thermoplastic toughening diluent.

[0011] Furthermore, the preparation method of the modified bisphenol A epoxy resin is:

[0012] (1) taking cellulose nanocrystals and adding water to prepare a cellulose nanocrystal aqueous dispersion;

[0013] (2) adjusting the pH value of the cellulose nanocrystal aqueous dispersion obtained in step (1) to 8-9, adding a pH buffer, adding tannic acid, and stirring for 20-30 hours to obtain a PTA@CNC aqueous dispersion;

[0014] (3) dissolving methacryloyl chloride in pyridine, and then mixing with the PTA@CNC aqueous dispersion obtained in step (2), and stirring at 45-60° C. for 20-30 hours, centrifuging the mixture, collecting the precipitate, and obtaining MC-PTA@CNC;

[0015] (4) dispersing the MC-PTA@CNC obtained in step (3) in ethanol, centrifuging, and drying to obtain hydrophobic nanomaterial MC-PTA@CNC powder;

[0016] (5) Add the hydrophobic nanomaterial MC-PTA@CNC powder obtained in step (4) to the solvent, stir evenly, heat to 55-65° C., add bisphenol A epoxy resin, ultrasonically stir for 25-35 minutes, and then heat to 140-160° C. to obtain modified bisphenol A epoxy resin.

[0017] The present invention uses the self-developed and synthesized hydrophobic nano material MC-PTA@CNC to modify the bisphenol A type epoxy resin. The hydrophobic nano material has good compatibility with the epoxy resin, so that it can be effectively embedded in the epoxy resin network, which helps to reduce defects in the composite material (i.e., blank spaces between molecules, where there is no interaction or weak interaction), and further improves the bonding force between the epoxy resin and other materials, which is specifically reflected in the improvement of the mechanical properties of the adhesive (hardness, adhesion, shear strength and flexural strength, etc.) and the reduction of the surface drying time.

[0018] Furthermore, the modified powder filler in the A component and the B component is prepared by modifying the powder filler with tannic acid and a silane coupling agent.

[0019] The present invention uses tannic acid and silane coupling agent to modify powder filler, which can not only improve the interface effect between powder filler and epoxy resin and curing agent, enhance its dispersibility, solve the problem of low interface force and poor dispersibility of powder filler in adhesive, but also play a role in enhancing the mechanical properties (hardness, adhesion, shear strength and bending strength, etc.) of adhesive. The structure of tannic acid is shown below.

[0020]

[0021] Furthermore, the powder filler is two or three of talcum powder, titanium dioxide and quartz powder.

[0022] Furthermore, the preparation method of the modified powder filler is:

[0023] Dissolve tannic acid and silane coupling agent in water to prepare an aqueous solution containing tannic acid and silane coupling agent, pour the prepared aqueous solution into the powder filler, stir and react for 20-40 minutes, then filter and dry.

[0024] Furthermore, the glycidyl ester epoxy resin in the component A is diglycidyl adipate; and the coupling agent in the component A is one or more of the silane coupling agents KH-550, KH-560, and KH-570.

[0025] Furthermore, the defoaming agent in the component A and the component B is dimethyl silicone oil; and the anti-settling agent in the component A and the component B is fumed silica.

[0026] Furthermore, the curing accelerator in the B component is curing accelerator DMP-30; and the thermoplastic toughening diluent in the B component is dibutyl phthalate.

[0027] Another object of the present invention is to provide a method for preparing the fast curing adhesive for cutting solar silicon wafers, comprising the following steps:

[0028] S1: adding modified bisphenol A epoxy resin, glycidyl ester epoxy resin, modified powder filler, defoamer, anti-settling agent, colorant and coupling agent into a stirring tank in sequence, and dispersing and stirring for 1-2 hours to obtain component A;

[0029] S2: adding polythiol, curing accelerator, defoamer, anti-settling agent, modified powder filler and thermoplastic toughening diluent into a stirring tank in sequence, and dispersing and stirring for 1-2 hours to obtain component B;

[0030] S3: Mix component A and component B in a ratio of 1:1-1.2 to obtain.

[0031] Compared with the prior art, the present invention has the following advantages:

[0032] (1) The fast curing adhesive stick for solar silicon wafer cutting prepared by the present invention has the advantages of high hardness, strong adhesion, high bonding shear strength, high bending strength, excellent mechanical properties, short surface drying time and high curing efficiency;

[0033] (2) The fast-curing adhesive for cutting solar silicon wafers prepared by the present invention can improve production efficiency and reduce the wire stripping rate, edge collapse rate and stick drop rate while achieving stable cutting;

[0034] (3) The glycidyl ester epoxy resin added in the present invention belongs to alicyclic epoxy resin, which is highly sensitive to moisture and temperature. In a humid and hot environment, the adhesive structure can be disintegrated at a relatively low temperature, resulting in loss of adhesion, thereby reducing the corrosiveness of the degumming liquid and helping to reduce the dirt caused by the degumming process. DETAILED DESCRIPTION

[0035] The present invention is further illustrated below through the description of specific implementation modes, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of ​​the present invention, but as long as they do not deviate from the basic idea of ​​the present invention, they are all within the scope of the present invention.

[0036] The raw materials used in the present invention are commercially available unless otherwise specified.

[0037] Reagents and instruments:

[0038] The bisphenol A epoxy resin was purchased from Nantong Xingchen Synthetic Materials Co., Ltd., model E-51, E-44;

[0039] The diglycidyl adipate was purchased from Wuhan Kemik Biopharmaceutical Technology Co., Ltd.

[0040] The silane coupling agents KH-550, KH-560 and KH-570 were purchased from Dongguan Kangjin New Material Technology Co., Ltd.

[0041] The methacryloyl chloride (MC) was purchased from Zhongshan Yuanda New Materials Co., Ltd.

[0042] The dibutyl phthalate was purchased from Jinan Weite Chemical Technology Co., Ltd., model MY-101;

[0043] The polythiol GL1820 and GL1810 were purchased from Guangzhou Green New Materials Co., Ltd.

[0044] The tannic acid (TA) and dopamine (DA) were purchased from Xi'an Xihai Biotechnology Co., Ltd.

[0045] The cellulose nanocrystals (CNC) were purchased from ScienceK;

[0046] The powder fillers include talcum powder, titanium dioxide and quartz powder purchased from Guangzhou Yifeng Chemical Technology Co., Ltd.

[0047] The defoaming agent dimethyl silicone oil was purchased from Hefei Yueguan New Materials Co., Ltd., model DE-0784;

[0048] The anti-settling agent fumed silica was purchased from Dongguan Jiran New Materials Co., Ltd., model K200;

[0049] The curing accelerator DMP-30 was purchased from Shanghai Hongzhuang Chemical Technology Co., Ltd.

[0050] The blue colorant was purchased from Jiangsu Jiayuancheng Biotechnology Co., Ltd., model JYC 66;

[0051] The pyridine, N,N-dimethylformamide (DMF), and tris(hydroxymethyl)aminomethane (Tris) were purchased from Aladdin;

[0052] Ultrasonic homogenizer equipment Shanghai Shengxi Ultrasonic Instruments Powerful Supplier, model FS-1200N.

[0053] Example 1: A fast-curing adhesive for cutting solar silicon wafers

[0054] The fast-curing adhesive stick for cutting solar silicon wafers comprises component A and component B, wherein component A comprises the following components and their weight fractions: 30 parts of modified E51 bisphenol A epoxy resin, 10 parts of modified E44 bisphenol A epoxy resin, 5 parts of diglycidyl adipate, 10 parts of modified talcum powder, 10 parts of modified quartz powder, 0.1 parts of dimethyl silicone oil, 0.05 parts of fumed silica, 0.05 parts of blue colorant, and 0.01 parts of silane coupling agent KH-550; and component B comprises the following components and their weight fractions: 35 parts of polythiol GL1820, 2 parts of curing accelerator DMP-30, 0.1 parts of dimethyl silicone oil, 0.05 parts of fumed silica, 8 parts of modified talcum powder, 1 part of modified titanium dioxide, 6 parts of modified quartz powder, and 5 parts of dibutyl phthalate.

[0055] The preparation method of modified E51 bisphenol A epoxy resin is as follows:

[0056] (1) adding water to cellulose nanocrystals in an amount of 49 times the mass of the cellulose nanocrystals, homogenizing for 10 minutes, and then ultrasonicating for 10 minutes to prepare a 2% by mass cellulose nanocrystal aqueous dispersion;

[0057] (2) adjusting the pH value of the cellulose nanocrystal aqueous dispersion obtained in step (1) to 8 using a 0.01% by mass sodium hydroxide aqueous solution, adding tris(hydroxymethylaminomethane) as a pH buffer, wherein the amount of tris(hydroxymethylaminomethane) added is 0.2% by mass of the cellulose nanocrystal aqueous dispersion, and adding tannic acid, wherein the amount of tannic acid added is 0.4% by mass of the cellulose nanocrystal aqueous dispersion, and stirring at room temperature for 24 hours to obtain a PTA@CNC aqueous dispersion;

[0058] (3) dissolving methacryloyl chloride in pyridine to prepare a methacryloyl chloride pyridine solution with a mass percentage of 2%, mixing the methacryloyl chloride pyridine solution with the PTA@CNC aqueous dispersion obtained in step (2) in equal volumes, stirring at 45° C. for 24 hours, centrifuging the mixture, collecting the precipitate, and obtaining MC-PTA@CNC;

[0059] (4) dispersing the MC-PTA@CNC obtained in step (3) in ethanol, centrifuging three times, and freeze-drying to obtain hydrophobic nanomaterial MC-PTA@CNC powder;

[0060] (5) Add the hydrophobic nanomaterial MC-PTA@CNC powder obtained in step (4) to N,N-dimethylformamide, wherein the mass volume ratio of the hydrophobic nanomaterial MC-PTA@CNC powder to N,N-dimethylformamide is 1:100 (g / mL), stir evenly, heat to 55°C, add E51 bisphenol A epoxy resin, wherein the amount of E51 bisphenol A epoxy resin added is 100 times the mass of MC-PTA@CNC powder, sonicate and stir for 30 minutes, then heat to 140°C to remove N,N-dimethylformamide, and obtain modified E51 bisphenol A epoxy resin.

[0061] The preparation method of the modified E44 bisphenol A epoxy resin is similar to the preparation method of the modified E51 bisphenol A epoxy resin, the only difference being that the E51 bisphenol A epoxy resin is replaced by the E44 bisphenol A epoxy resin.

[0062] The preparation method of the modified talcum powder is:

[0063] Dissolve tannic acid and silane coupling agent in water to prepare an aqueous solution containing tannic acid and silane coupling agent KH-550, the mass percentage of tannic acid in the aqueous solution is 1%, the mass percentage of silane coupling agent in the aqueous solution is 0.5%, pour the prepared aqueous solution into the powder filler talcum powder, the mass ratio of the aqueous solution to the powder filler is 2:1, stir and react for 30 minutes, filter and dry.

[0064] The preparation method of the modified titanium dioxide and modified quartz powder is similar to the preparation method of the modified talc powder, and the only difference is that the powder filler talc powder is replaced by powder filler titanium dioxide or powder filler quartz powder.

[0065] The method for preparing the fast-curing adhesive stick for cutting solar silicon wafers comprises the following steps:

[0066] S1: Add modified E51 bisphenol A epoxy resin, modified E44 bisphenol A epoxy resin, diglycidyl adipate, modified talc, modified quartz powder, dimethyl silicone oil, fumed silica, blue colorant and silane coupling agent KH-550 into a stirring tank in sequence, and disperse and stir for 1 hour to obtain component A;

[0067] S2: add polythiol GL1820, curing accelerator DMP-30, dimethyl silicone oil, fumed silica, modified talcum powder, modified titanium dioxide, modified quartz powder and dibutyl phthalate into a stirring tank in sequence, disperse and stir for 1 hour to obtain component B;

[0068] S3: Mix component A and component B in a ratio of 1:1.

[0069] Example 2: A fast-curing adhesive for cutting solar silicon wafers

[0070] The fast-curing adhesive stick for cutting solar silicon wafers comprises component A and component B, wherein component A comprises the following components and their weight fractions: 50 parts of modified E51 bisphenol A epoxy resin, 20 parts of modified E44 bisphenol A epoxy resin, 15 parts of diglycidyl adipate, 20 parts of modified talcum powder, 20 parts of modified quartz powder, 3 parts of dimethyl silicone oil, 5 parts of fumed silica, 1 part of blue colorant, and 3 parts of silane coupling agent KH-560; and component B comprises the following components and their weight fractions: 60 parts of polythiol GL1810, 10 parts of curing accelerator DMP-30, 3 parts of dimethyl silicone oil, 5 parts of fumed silica, 16 parts of modified talcum powder, 2 parts of modified titanium dioxide, 12 parts of modified quartz powder, and 20 parts of dibutyl phthalate.

[0071] The preparation method of the modified E51 bisphenol A epoxy resin is as follows:

[0072] (1) adding water to cellulose nanocrystals in an amount of 49 times the mass of the cellulose nanocrystals, homogenizing for 10 minutes, and then ultrasonicating for 10 minutes to prepare a 2% by mass cellulose nanocrystal aqueous dispersion;

[0073] (2) adjusting the pH value of the cellulose nanocrystal aqueous dispersion obtained in step (1) to 8 using a 0.01% by mass sodium hydroxide aqueous solution, adding tris(hydroxymethylaminomethane) as a pH buffer, wherein the amount of tris(hydroxymethylaminomethane) added is 0.2% by mass of the cellulose nanocrystal aqueous dispersion, and adding tannic acid, wherein the amount of tannic acid added is 0.4% by mass of the cellulose nanocrystal aqueous dispersion, and stirring at room temperature for 24 hours to obtain a PTA@CNC aqueous dispersion;

[0074] (3) dissolving methacryloyl chloride in pyridine to prepare a methacryloyl chloride pyridine solution with a mass percentage of 2%, mixing the methacryloyl chloride pyridine solution with the PTA@CNC aqueous dispersion obtained in step (2) in equal volumes, stirring at 45° C. for 24 hours, centrifuging the mixture, collecting the precipitate, and obtaining MC-PTA@CNC;

[0075] (4) dispersing the MC-PTA@CNC obtained in step (3) in ethanol, centrifuging three times, and freeze-drying to obtain hydrophobic nanomaterial MC-PTA@CNC powder;

[0076] (5) Add the hydrophobic nanomaterial MC-PTA@CNC powder obtained in step (4) to N,N-dimethylformamide, wherein the mass volume ratio of the hydrophobic nanomaterial MC-PTA@CNC powder to N,N-dimethylformamide is 1:100 (g / mL), stir evenly, heat to 55°C, add E51 bisphenol A epoxy resin, wherein the amount of E51 bisphenol A epoxy resin added is 100 times the mass of MC-PTA@CNC powder, sonicate and stir for 30 minutes, then heat to 150°C to remove N,N-dimethylformamide, and obtain modified E51 bisphenol A epoxy resin.

[0077] The preparation method of the modified E44 bisphenol A epoxy resin is similar to the preparation method of the modified E51 bisphenol A epoxy resin, the only difference being that the E51 bisphenol A epoxy resin is replaced by the E44 bisphenol A epoxy resin.

[0078] The preparation methods of the modified talcum powder, modified titanium dioxide and modified quartz powder are the same as those in Example 1.

[0079] The method for preparing the fast-curing adhesive stick for cutting solar silicon wafers comprises the following steps:

[0080] S1: Add modified E51 bisphenol A epoxy resin, modified E44 bisphenol A epoxy resin, diglycidyl adipate, modified talcum powder, modified quartz powder, dimethyl silicone oil, fumed silica, blue colorant and silane coupling agent KH-560 into a stirring tank in sequence, and disperse and stir for 1 hour to obtain component A;

[0081] S2: add polythiol GL1810, curing accelerator DMP-30, dimethyl silicone oil, fumed silica, modified talcum powder, modified titanium dioxide, modified quartz powder and dibutyl phthalate into a stirring tank in sequence, disperse and stir for 1 hour to obtain component B;

[0082] S3: Mix component A and component B in a ratio of 1:1.

[0083] Example 3: A fast-curing adhesive for cutting solar silicon wafers

[0084] The fast-curing adhesive stick for cutting solar silicon wafers comprises component A and component B, wherein component A comprises the following components and their weight fractions: 48 parts of modified E51 bisphenol A epoxy resin, 10 parts of modified E44 bisphenol A epoxy resin, 8 parts of diglycidyl adipate, 18 parts of modified talcum powder, 12 parts of modified quartz powder, 1.2 parts of dimethyl silicone oil, 0.4 parts of fumed silica, 0.4 parts of blue colorant, and 2 parts of silane coupling agent KH-550; and component B comprises the following components and their weight fractions: 55 parts of polythiol GL1810, 5 parts of curing accelerator DMP-30, 1 part of dimethyl silicone oil, 2 parts of fumed silica, 13.5 parts of modified talcum powder, 1.5 parts of modified titanium dioxide, 10 parts of modified quartz powder, and 12 parts of dibutyl phthalate;

[0085] The preparation method of the modified E51 bisphenol A epoxy resin is as follows:

[0086] (1) adding water to cellulose nanocrystals in an amount of 49 times the mass of the cellulose nanocrystals, homogenizing for 10 minutes, and then ultrasonicating for 10 minutes to prepare a 2% by mass cellulose nanocrystal aqueous dispersion;

[0087] (2) adjusting the pH value of the cellulose nanocrystal aqueous dispersion obtained in step (1) to 8.5 using a 0.01% by mass sodium hydroxide aqueous solution, adding tris(hydroxymethylaminomethane) as a pH buffer, the amount of tris(hydroxymethylaminomethane) added being 0.2% by mass of the cellulose nanocrystal aqueous dispersion, adding tannic acid, the amount of tannic acid added being 0.4% by mass of the cellulose nanocrystal aqueous dispersion, and stirring at room temperature for 24 hours to obtain a PTA@CNC aqueous dispersion;

[0088] (3) dissolving methacryloyl chloride in pyridine to prepare a methacryloyl chloride pyridine solution with a mass percentage of 2%, mixing the methacryloyl chloride pyridine solution with the PTA@CNC aqueous dispersion obtained in step (2) in equal volumes, stirring at 45° C. for 24 hours, centrifuging the mixture, collecting the precipitate, and obtaining MC-PTA@CNC;

[0089] (4) dispersing the MC-PTA@CNC obtained in step (3) in ethanol, centrifuging three times, and freeze-drying to obtain hydrophobic nanomaterial MC-PTA@CNC powder;

[0090] (5) Add the hydrophobic nanomaterial MC-PTA@CNC powder obtained in step (4) to N,N-dimethylformamide, wherein the mass volume ratio of the hydrophobic nanomaterial MC-PTA@CNC powder to N,N-dimethylformamide is 1:100 (g / mL), stir evenly, heat to 55°C, add E51 bisphenol A epoxy resin, wherein the amount of E51 bisphenol A epoxy resin added is 100 times the mass of MC-PTA@CNC powder, sonicate and stir for 30 minutes, then heat to 150°C to remove N,N-dimethylformamide, and obtain modified E51 bisphenol A epoxy resin.

[0091] The preparation method of the modified E44 bisphenol A epoxy resin is similar to the preparation method of the modified E51 bisphenol A epoxy resin, the only difference being that the E51 bisphenol A epoxy resin is replaced by the E44 bisphenol A epoxy resin.

[0092] The preparation methods of the modified talcum powder, modified titanium dioxide and modified quartz powder are the same as those in Example 1.

[0093] The method for preparing the fast-curing adhesive stick for cutting solar silicon wafers comprises the following steps:

[0094] S1: Add modified E51 bisphenol A epoxy resin, modified E44 bisphenol A epoxy resin, diglycidyl adipate, modified talc, modified quartz powder, dimethyl silicone oil, fumed silica, blue colorant and silane coupling agent KH-550 into a stirring tank in sequence, and disperse and stir for 1 hour to obtain component A;

[0095] S2: add polythiol GL1810, curing accelerator DMP-30, dimethyl silicone oil, fumed silica, modified talcum powder, modified titanium dioxide, modified quartz powder and dibutyl phthalate into a stirring tank in sequence, disperse and stir for 1 hour to obtain component B;

[0096] S3: Mix component A and component B in a ratio of 1:1.

[0097] Comparative Example 1: A sticky glue

[0098] The composition of the stick glue is similar to that of Example 3.

[0099] The difference from Example 3 is that the bisphenol A epoxy resin is modified using MC-PDA@CNC, and the preparation method of MC-PDA@CNC is similar to that of MC-PTA@CNC, except that tannic acid is replaced with dopamine. The reaction route is shown below. The functional groups of dopamine are mainly amino groups and catechol groups, and the structure is similar to that of tannic acid. When the pH value is about 8.5, it can undergo a self-polymerization reaction similar to that of tannic acid to generate PDA.

[0100]

[0101] Comparative Example 2: A sticky glue

[0102] The composition of the stick glue is similar to that of Example 3.

[0103] The difference from Example 3 is that the powder filler is modified by using dopamine and a silane coupling agent.

[0104] Test Example 1: Performance test of stick glue

[0105] 1. Test samples: the fast-curing adhesive sticks for cutting solar silicon wafers prepared in Examples 1, 2 and 3, and the adhesive sticks prepared in Comparative Examples 1-2.

[0106] 2. Test methods:

[0107] According to national standards, the surface drying time and the performance after curing of the adhesive sticks prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested.

[0108] (1) Tensile strength test

[0109] The tensile strength is tested according to the standard GB / T 30776-2014.

[0110] (2) Shear strength

[0111] The shear strength is tested using GB / T 7124-2008.

[0112] (3) Elongation at break test

[0113] The elongation at break is tested according to the standard GB / T 30776-2014.

[0114] (4) Adhesion test

[0115] Adhesion is tested according to standard GB / T 5210-2006.

[0116] (5) Initial curing time test

[0117] The initial surface drying time is tested according to the standard GB / T 13477.5-2002.

[0118] (6) Shore hardness test

[0119] The Shore hardness is tested according to the standard GB / T 2411-2008.

[0120] 3. The performance test results of the sticky adhesives prepared in Examples 1 to 3 and Comparative Examples 1 to 2 are shown in Table 1.

[0121] Table 1: Performance test results of the stick glue obtained in Examples 1 to 3 and Comparative Examples 1 to 2

[0122]

[0123] As can be seen from Table 1, the sticky glue prepared in Example 1, Example 2, and Example 3 of the present invention has the advantages of high hardness, strong adhesion, and high (bonding) shear strength, among which Example 3 has the best effect and is the best embodiment of the present invention. The (bonding) shear strength, 2h Shore hardness, tensile strength, (toughness) elongation at break, and adhesion of the sticky glue prepared in Example 3 of the present invention are higher than those of the sticky glue prepared in Comparative Example 1 and Comparative Example 2, and the surface drying time of the sticky glue prepared in Example 3 is lower than that of the sticky glue prepared in Comparative Example 1 and Comparative Example 2. It can be seen that the sticky glue prepared in the present invention has the advantages of high hardness, strong adhesion, high (bonding) shear strength, excellent mechanical properties, and short surface drying time.

[0124] Test Example 2: Cutting Performance Test

[0125] The stick adhesives prepared in Examples 1 to 3 and Comparative Examples 1 to 2, as well as conventional stick adhesives available on the market, were used to bond silicon sticks, and then cut after curing. The test results of the cutting performance on a machine are shown in Table 2 below.

[0126] Table 2: Cutting performance test results on the machine

[0127]

[0128] It can be seen from the test results in Table 2 that the wire-shedding rate, edge-breakage rate and stick-dropping rate of the stick adhesive prepared by the present invention are significantly lower than those of Comparative Example 1, Comparative Example 2, conventional stick adhesive 1 and conventional stick adhesive 2. The stick adhesive prepared by the present invention can effectively solve the problems of low production efficiency, wire-shedding rate (the adhesive wire falls off the plastic plate and adheres to the silicon wafer), edge-breakage rate and stick-dropping rate in the silicon wafer cutting process.

[0129] In summary, the fast-curing adhesive stick for cutting solar silicon wafers prepared by the present invention has the advantages of high hardness, strong adhesion, high (bonding) shear strength, etc., excellent mechanical properties, short surface drying time, and high curing efficiency; the fast-curing adhesive stick for cutting solar silicon wafers prepared by the present invention can improve production efficiency and reduce wire breaking rate, edge collapse rate and stick falling rate while achieving stable cutting.

[0130] Those skilled in the art should understand that the above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by those with ordinary knowledge in the art without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention.

Claims

1. A fast curing adhesive for cutting solar silicon wafers, comprising component A and component B, characterized in that: The component A comprises modified bisphenol A epoxy resin, glycidyl ester epoxy resin, modified powder filler, defoamer, anti-settling agent, colorant and coupling agent; the component B comprises polythiol, curing accelerator, defoamer, anti-settling agent, modified powder filler and thermoplastic toughening diluent; The modified bisphenol A epoxy resin is prepared by modifying bisphenol A epoxy resin with a hydrophobic nano material; the hydrophobic nano material is prepared by modifying cellulose nanocrystals with tannic acid and methacryloyl chloride; The preparation method of the modified bisphenol A epoxy resin is: (1) taking cellulose nanocrystals and adding water to prepare a cellulose nanocrystal aqueous dispersion; (2) adjusting the pH value of the cellulose nanocrystal aqueous dispersion obtained in step (1) to 8-9, adding a pH buffer and tannic acid, and stirring for 20-30 hours to obtain a PTA@CNC aqueous dispersion; (3) dissolving methacryloyl chloride in pyridine, and then mixing it with the PTA@CNC aqueous dispersion obtained in step (2), and stirring at 45-60° C. for 20-30 hours, centrifuging the mixture, collecting the precipitate, and obtaining MC-PTA@CNC; (4) dispersing the MC-PTA@CNC obtained in step (3) in ethanol, centrifuging, and drying to obtain hydrophobic nanomaterial MC-PTA@CNC powder; (5) adding the hydrophobic nanomaterial MC-PTA@CNC powder obtained in step (4) to the solvent, stirring evenly, heating to 55-65° C., adding bisphenol A epoxy resin, ultrasonically stirring for 25-35 minutes, and then heating to 140-160° C. to obtain modified bisphenol A epoxy resin; The modified powder fillers in the A component and the B component are prepared by modifying the powder fillers with tannic acid and a silane coupling agent.

2. The fast curing adhesive for cutting solar silicon wafers according to claim 1, characterized in that: The component A comprises the following components and their weight fractions: 40-70 parts of modified bisphenol A epoxy resin, 5-20 parts of glycidyl ester epoxy resin, 20-40 parts of modified powder filler, 0.1-3 parts of defoamer, 0.05-5 parts of anti-settling agent, 0.05-1 parts of colorant and 0.01-3 parts of coupling agent; the component B comprises the following components and their weight fractions: 35-60 parts of polythiol, 2-10 parts of curing accelerator, 0.1-3 parts of defoamer, 0.05-5 parts of anti-settling agent, 15-30 parts of modified powder filler and 5-20 parts of thermoplastic toughening diluent.

3. The fast curing adhesive for cutting solar silicon wafers according to claim 1, characterized in that: The powder filler is two or three of talcum powder, titanium dioxide and quartz powder.

4. The fast curing adhesive stick for cutting solar silicon wafers according to claim 1, characterized in that: The preparation method of the modified powder filler is: Dissolve tannic acid and silane coupling agent in water to prepare an aqueous solution containing tannic acid and silane coupling agent, pour the prepared aqueous solution into the powder filler, stir and react for 20-40 minutes, then filter and dry.

5. The fast curing adhesive stick for cutting solar silicon wafers according to claim 1 or 2, characterized in that: The glycidyl ester epoxy resin in the component A is diglycidyl adipate; the coupling agent in the component A is one or more of the silane coupling agents KH-550, KH-560, and KH-570.

6. The fast curing adhesive stick for cutting solar silicon wafers according to claim 1 or 2, characterized in that: The defoaming agent in the component A and the component B is dimethyl silicone oil; the anti-settling agent in the component A and the component B is fumed silica.

7. The fast curing adhesive for cutting solar silicon wafers according to claim 1 or 2, characterized in that: The curing accelerator in the B component is curing accelerator DMP-30; the thermoplastic toughening diluent in the B component is dibutyl phthalate.

8. The method for preparing the fast curing adhesive stick for cutting solar silicon wafers according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: adding modified bisphenol A epoxy resin, glycidyl ester epoxy resin, modified powder filler, defoamer, anti-settling agent, colorant and coupling agent into a stirring tank in sequence, and dispersing and stirring for 1-2 hours to obtain component A; S2: adding polythiol, curing accelerator, defoamer, anti-settling agent, modified powder filler and thermoplastic toughening diluent into a stirring tank in sequence, and dispersing and stirring for 1-2 hours to obtain component B; S3: Mix component A and component B in a ratio of 1:1-1.2 to obtain.

Citation Information

Patent Citations

  • Rod-sticking adhesive for slicing thinning silicon sliced sheets and preparation method of rod-sticking adhesive

    CN110437779A

  • Preparation method for straw-based crystalline cellulose nanocrystals and rubber composite material of straw-based crystalline cellulose nanocrystals

    CN105419012A

  • Sticking glue for diamond wire silicon slice and preparation method

    CN109880567A